2016
DOI: 10.1080/00140139.2016.1245874
|View full text |Cite
|
Sign up to set email alerts
|

Is three the magic number? The role of ergonomic principles in cross country comprehension of road traffic signs

Abstract: Article:Jamson, SL orcid.org/0000-0001-8166-0403 and Mrozek, M (2016) Is three the magic number? The role of ergonomic principles in cross country comprehension of road traffic signs. Ergonomics, 60 (7 ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 27 publications
1
10
0
1
Order By: Relevance
“…However, no such differences were found in relation to the other groups of non-standard signs analyzed. The result of our study is consistent with several other studies [16,17,19].…”
Section: Discussion Of Research Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…However, no such differences were found in relation to the other groups of non-standard signs analyzed. The result of our study is consistent with several other studies [16,17,19].…”
Section: Discussion Of Research Resultssupporting
confidence: 94%
“…This could have had a negative impact on their comprehension. Jamson and Mrozek [19] have already observed this problem, pointing to the need to standardize traffic signs in terms of color, shape and their physical and spatial features. It seems that it is also important to take into account the meaning of the symbol itself (shape, color, message model) in the designing process.…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The design features found in directional signs have standards and requirements to be able to relay or deliver the message to road users with comfort and safety. (Jamson & Mrozek, 2017) studied responses of drivers from 3 different countries and concluded that text colors and shapes standards are the most defining criteria for aiding drivers' comprehension.…”
Section: Designmentioning
confidence: 99%
“…Several researchers have investigated how the principles and guidelines of HFE should be applied to assist in the process of designing or re-designing products and services. Studies of several areas of knowledge, such as medication alerts [1,2]; traffic signs [3,4]; classrooms [5,6]; sustainable buildings [7]; musculoskeletal disorders [8]; furniture [9]; workplaces [10,11]; and healthcare [12] have found that the application of HFE principles and/or guidelines can improve the performance and usability of products and services.…”
Section: Introductionmentioning
confidence: 99%